2020
DOI: 10.1249/mss.0000000000002147
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Evaluation of Current Methods for Exercise Prescription in Women and Men

Abstract: Common methods to prescribe exercise intensity are based on fixed percentages of maximum rate of oxygen uptake (V˙O2max), peak work rate (WRpeak), maximal HR (HRmax). However, it is unknown how these methods compare to the current models to partition the exercise intensity spectrum. Purpose Thus, the aim of this study was to compare contemporary gold-standard approaches for exercise prescription based on fixed percentages of maximum values to the well-established, but underut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
150
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(163 citation statements)
references
References 49 publications
12
150
0
1
Order By: Relevance
“…From a practical point of view the heterogenous character of HRPC's has some consequences on exercise prescription when using fixed percentage of HR max , already discussed in detail by our study group (2,12) which was supported recently by Iannetta et al (37). We could nicely show that the same relative intensity of 85% HR max gave different workloads when related to the anaerobic threshold and this effect became even stronger with ß 1 -recepter antagonism application (13).…”
Section: Exercise Prescriptionsupporting
confidence: 81%
See 2 more Smart Citations
“…From a practical point of view the heterogenous character of HRPC's has some consequences on exercise prescription when using fixed percentage of HR max , already discussed in detail by our study group (2,12) which was supported recently by Iannetta et al (37). We could nicely show that the same relative intensity of 85% HR max gave different workloads when related to the anaerobic threshold and this effect became even stronger with ß 1 -recepter antagonism application (13).…”
Section: Exercise Prescriptionsupporting
confidence: 81%
“…Underestimation might cause absence of desired training effects, but overestimation of the workload presents some risks and could have major consequences in subjects suffering from a chronic disease. Iannetta et al (37) supported this earlier results and concluded that "contemporary gold-standard methods for exercise prescription based on fixedpercentages of maximum values conform poorly to exercise intensity domains and thus do not adequately control the metabolic stimulus. "…”
Section: Exercise Prescriptionmentioning
confidence: 85%
See 1 more Smart Citation
“…The use of an INC-derived fixed percentage to calculate the HIIT work rate should be considered another determinant of the variability in R lim results in this context. In 2019, Iannetta et al [64] reported that when work rates are set as fixed-percentage of parameters measured at maximal exercise capacity, given the betweensubjects variability in percentages defining the intensity of an exercise domain (i.e., moderate, heavy, severe, extreme [65]), an increased variance in metabolic stimulus/response is expected. In our study, this correlates to metabolic stress and unequal relative work seen in the HIIT participants' responses (e.g., oxygen uptake ranged between 82-91% and 95.4-112% of the individual _ VO 2max during the first and following HIIT repetitions, respectively; Fig 4A).…”
Section: Plos Onementioning
confidence: 99%
“…In our study, this correlates to metabolic stress and unequal relative work seen in the HIIT participants' responses (e.g., oxygen uptake ranged between 82-91% and 95.4-112% of the individual _ VO 2max during the first and following HIIT repetitions, respectively; Fig 4A). To ensure accurate control of exercise intensity among participants and reduce errors in comparisons, future studies on the physiological response at specific exercise intensity domains should adopt methodological approaches that consider individual physiological thresholds and exercise-intensity domain models as those proposed by Iannetta and colleagues [64].…”
Section: Plos Onementioning
confidence: 99%